Clinical Translation of an Insertion Tool for Minimally Invasive Cochlear Implant Surgery - Riojas, Katherine E. (J Med Device, 2021)
The objective of this paper is to describe the development of a minimally invasive cochlear implant surgery (MICIS) electrode array insertion tool concept to enable clinical translation. First, analysis of the geometric parameters of potential MICIS patients (N = 97) was performed to inform tool design, inform MICIS phantom model design, and provide further insight into MICIS candidacy. Design changes were made to the insertion tool based on clinical requirements and parameter analysis results. A MICIS phantom testing model was built to evaluate insertion force profiles in a clinically realistic manner, and the new tool design was evaluated in the model and in cadavers to test clinical viability. Finally, after regulatory approval, the tool was used for the first time in a clinical case. Results of this work included first, in the parameter analysis, approximately 20% of the population was not considered viable MICIS candidates. Additionally, one 3D printed tool could accommodate all viable candidates with polyimide sheath length adjustments accounting for interpatient variation. The insertion tool design was miniaturized out of clinical necessity and a disassembly method, necessary for removal around the cochlear implant, was developed and tested. Phantom model testing revealed that the force profile of the insertion tool was similar to that of traditional forceps insertion. Cadaver testing demonstrated that all clinical requirements (including complete disassembly) were achieved with the tool, and the new tool enabled 15% deeper insertions compared to the forceps approach. Finally, and most importantly, the tool helped achieve a full insertion in its first MICIS clinical case. In conclusion, the new insertion tool provides a clinically viable solution to one of the most difficult aspects of MICIS.